Religious Coping and Depression in Young Adulthood: Effects of Global Stress Exposure and Pre-Teenage Religious Service Attendance - Eliassen, A. Henry (Review of religious research, 2013)
This paper builds upon previous research on the association between religiosity and depressive symptomatology in young adults by focusing on the coping aspects of religious involvement (use of beliefs, comfort seeking, and prayer). Data come from a representative sample of Miami-Dade County, Florida, youths interviewed initially at around age 11 and then at age 19 to 21 (N = 1,210). OLS regression models demonstrate an inverted U-shaped curvilinear relationship between religious coping and depression which, in subgroup analyses, applies only to females, and specifically to those young women reporting above-average stress exposure who had attended religious services at least once a week during their middle school years. No association is found among those reporting lower stress exposure or less frequent pre-teenage service attendance. These results provide evidence that early religious exposure on a regular basis and high global stress exposure may be essential preconditions for a relationship at the aggregate level between current religious coping and depressive symptomatology in young adults.